Geopolitics of Vaccines: War by Other Means? - Vankovska, Biljana (Филозофски факултет, УКИМ, 2021)
The article sheds light on the causes, consequences, and possible scenarios of the geopolitics of vaccines. Given the international context and domination of structural violence and clashes of great powers on the global faultlines, no wonder that the vaccines have turned into a power politics tool rather than a global public good and an asset to save lives. Furthermore, private corporations have strengthened their grip on the states and their populations, while the state leaderships of the rich countries ride on the wave of vaccine nationalism and overt discrimination of others. The issue of quality, availability and distribution of anti-Covid-19 vaccines just offers a glimpse into an apocalyptic future – unless something is done soon to re-shape both State and the world order. The research sources are media-based but from a variety of geographical areas. Also, they are correlated with available academic analyses and findings concerning the so-called pandemopolitics, i.e. international and state politics in the time of the pandemic.
Keywords: geopolitics, vaccines, covid-19, power relations, capitalism, State